Muslim Minorities in Janji Matogu, Toba: A Historical Analysis of Socio-Religious Existence and Cultural Adaptation (1970–2020) - Muhammad Hasiando Nasution; Nursapia Harahap (Al-Mubin, 2026)
This study aims to analyze the existence and socio-religious dynamics of the Muslim minority community in Janji Matogu Village, Toba Regency, from 1970-2020. The primary focus of this research is the cultural adaptation process carried out by the Muslim community amidst a Christian majority environment deeply rooted in Batak customs. The research employs the historical method, consisting of four stages: heuristics, verification, interpretation, and historiography. Data were collected through in-depth interviews with religious and traditional leaders, field observations, and searches of local historical documents. The results indicate that the existence of Muslims in Janji Matogu is maintained through a “social syncretism” strategy, where Islamic identity is preserved without abandoning the values of Dalihan Na Tolu. The dynamics over five decades show a shift from mere survival to the strengthening of educational institutions and places of worship in harmony. This study concludes that cultural adaptation is the key to social integration, proving that differences in belief do not hinder community cohesion within the framework of inclusive Toba local wisdom.